Increased Weight Gain Difference Between A Monthly Injectable Contraception Acceptors with Three Monthly at Puskesmas II Denpasar Selatan - Ni Putu Prima Wulandari (Coping: Community of Publishing in Nursing, 2013)
Contraception is the efforts to prevent pregnancy. Popular contraceptive in Indonesia are injectable contraception. Injectable contraception contain the hormones progesterone and estrogen. Side effects of injectable contraception is the highest frequency of weight gain. Increased uncontrolled weight can lead to disease risk, such as coronary heart disease and diabetes mellitus. This study aims to determine weight gain difference between a monthly injectable contraception acceptors with three monthly at Puskesmas II Denpasar Selatan. This study uses descriptive comparative research and cross-sectional model approach with a sample of 60 people selected by purposive sampling. The results of the 30 respondents who belong to the one monthly  injectable contraception acceptor 28 respondents (93.3%) experienced weight gain, as well as on the three monthly injectable contraception acceptors from 30 respondents, 28 respondents (93.3%) had weight gain. Analysis of test results obtained using the Mann Whitney Test Asymp value. Sig. (2-tailed) of 0.608 which has a value greater than ? study (0.05) which indicates there are no significant differences, so that Ho received which means there is no difference in weight gain between a monthly injectable contraceptive acceptors with three monthly at Puskesmas II Denpasar Selatan. Based on the results obtained, the expected health care workers to provide adequate information and provide options to the acceptor for the proper use of contraception methods, so that the acceptor is not wrong in choosing a contraceptive method.